Four Job Satisfaction’s dimensions of secondary education teachers: An Exploratory Factor Analysis based on a Greek sample - Lavidas, Konstantinos; Dalapa, Mina; Dimitriadou, Stavroula; Athanassopoulos, Stavros (Preschool and Primary Education, 2019)
Background Surveying and assessing teachers’ job satisfaction constitutes an evergreen crosscutting issue. It deploys the formation of policies that underpin its’ augmentation aiming for enhanced educational outcomes. Internationally there are not many valid instruments that can be used to assess teachers’ job satisfaction. Especially in Greece, research on the reliability and validity of these instruments when applied on teachers is non-existent. Method The instrument used was JSS. JSS describes nine (9) dimensions of Job Satisfaction. 177 secondary education teachers in Western Greece took part in this research. Exploratory Factor Analyses was conducted. Results Parallel analyses and principal axis factoring revealed a structure of 4 dimensions of the JSS. Confirmatory factor analysis ascertained this structure that features satisfactory reliability and construct validity. Conclusions We could say that the JSS, according to the factorial structure, could be considered an appropriate tool for investigating the JS of teachers in Greece as well. The four -dimensions of the JSS revealed by the answers of Greek secondary education teachers are: teachers’ Payment framework, teachers’ Supervision, Nature of work and teachers’ Communication.